Determining the impact of plastering materials on temperature distribution in lightweight concrete enclosure structures exposed to fire - Bula, Serhiy (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is lightweight concrete wall structures treated with various types of conventional plasters. The problem addressed in the paper is to determine the effectiveness of different types of plastering to protect walls from the effects of high temperatures and improve the fire resistance of structures. The samples of one series were fabricated by plastering the aerated concrete wall with a cement-lime plaster while the samples of the other series were plastered with vermiculite-perlite plaster. Samples of the third series were made without plastering (control series). In accordance with the research program, the distribution of temperatures under fire load was determined for all series. Studies have shown that wall structures plastered with verliculite-perlite mortar demonstrated 3.8 times better thermal insulation characteristics compared to plastering with cement-lime mortar. The fire protection effect of plastering (compared to non-plastered samples) for vermiculite-perlite solution was 6.3 times, and for cement-lime – 1.6. Adhesion failure was observed in cement-lime plaster under high temperatures, highlighting the need for additional fixing when applied to lightweight concrete walls. Theoretical analysis of the results revealed a discrepancy of up to 19 % with the experimental findings. The high thermal insulation properties of vermiculite-perlite plasters in comparison with cement-lime plasters are well known. A distinctive feature of this study is the quantitative determination of temperature distribution for the investigated plasters under conditions approximating real fire exposure. The findings of this research can be applied to the design of buildings and structures requiring enhanced fire resistance for wall systems